Childhood cancer patients' experiences of a structured exercise program. A qualitative study using reflexive thematic analysis - Wilke, Dennis; Paul, Norbert W.; Dreismickenbecker, Elias; Alt, Francesca; Neu, Marie A.; Faber, Jörg (Frontiers in Pediatrics, 2025)
IntroductionUndergoing cancer treatment as a child, adolescent or young adult involves decreased physical activity and fitness, which may further compromise the bodily and psychosocial well-being of young patients. As an element of supportive care, exercise interventions may counteract these adverse effects. However, knowledge about the impact of such interventions, and of patients' and parents' experiences of participation, is only beginning to emerge.ObjectivesTo explore patients' and parental experiences of participating in a structured, individualized exercise program lasting 8–10 weeks during intensive treatment in a German childhood cancer center as part of the clinical trial FORTEe – Get strong to fight childhood cancer.MethodsWe conducted open qualitative interviews (n = 11) with children and adolescents (n = 6) and parents (n = 5), as well as participant observation during exercise sessions (n = 10). We used reflexive thematic analysis, as developed by Braun and Clarke, as our method of analysis.ResultsWe generated three themes: 1. Feeling better in my body and experiencing my physical capabilities; 2. Gaining distance from illness and treatment; and 3. Being recognized and involved as a vulnerable and individual patient. Moreover, we gained insights, regarding the burdensome impact of childhood cancer, and limitations of the exercise intervention. Participants reported almost exclusively positive experiences of participating in the program, which yielded benefits for the patients' physical fitness and capabilities, their bodily and psychological well-being and everyday life situation.ConclusionThis study supports the suitability and importance of making exercise therapy an integral element of supportive care for childhood cancer patients. Its insights may be helpful for health care professionals who plan on implementing, or who are involved in providing exercise interventions, as well as for scientists who accompany such interventions with qualitative research.